A Comparison of Voice Recognition Program and Traditional Keyboard Charting for Nurse Documentation - Mayer, LeAnn; Xu, Dongjuan; Edwards, Nancy; Bokhart, Gordon (Computers, informatics, nursing, 2021)
The purposes of this study are threefold: (1) compare the document times between a voice recognition system and keyboard charting, (2) compare the number of errors between the two methods, and (3) identify factors influencing documentation time. Voice recognition systems are considered a potential solution to decrease documentation time. However, little is known to what extent voice recognition systems can save nurses' documentation time. A pilot, simulation study was conducted using a voice recognition system and keyboard charting with 15 acute care nurses. A crossover method with repeated measures was utilized. Each nurse was given two simple and two complex assessment scenarios, assigned in random order, to document using both methods. Paired t-tests and multivariate linear regression models were used for data analysis. The voice recognition method saved the nurses 2.3 minutes (simple scenario) and 6.1 minutes (complex scenario) on average and was statistically significant (P < .001). There were no significant differences in errors or factors identified influencing documentation times. Eighty percent reported a preference of using voice recognition systems, and 87% agreed this method helped speed up charting. This study can show how a voice recognition system can improve documentation times compared with keyboard charting while still having thorough documentation.